2022
DOI: 10.3390/jcm11102787
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Mass Index and Renal Outcomes Modified by Chronic Kidney Disease and Anemia: The Obesity Paradox for Renal Outcomes

Abstract: Obesity-related nephropathy is associated with renal function progression. However, some studies have associated a high body mass index (BMI) with improved renal outcomes—this is referred to as the obesity paradox for renal outcomes, especially in relation to advanced chronic kidney disease (CKD). Central obesity can explain the obesity paradox in all-cause mortality. However, whether obesity or central obesity is associated with renal outcomes (renal replacement therapy or a 50% decline in the estimated glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…demonstrated that high BMI was associated with CKD progression in patients with CKD stage 3 but not in stage 4 38 . Our previous study also showed a similar result 17 . Thus, one study from Taiwan found that the impact of MetS in CKD progression became insignificant in patients with stage 4–5 CKD.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…demonstrated that high BMI was associated with CKD progression in patients with CKD stage 3 but not in stage 4 38 . Our previous study also showed a similar result 17 . Thus, one study from Taiwan found that the impact of MetS in CKD progression became insignificant in patients with stage 4–5 CKD.…”
Section: Discussionsupporting
confidence: 66%
“…The study conducted by Pammer et al, 13 Our previous study also showed a similar result. 17 Thus, one study from Taiwan found that the impact of MetS in CKD progression became insignificant in patients with stage 4-5 CKD. They interpreted the result as a paradoxical phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations